EVALUATION OF EFFICACY OF BACTERIAL CONSORTIUM B3RVY 3 FOR REMOVAL OF TOXICITY FROM DIFFERENT TEXTILE DYES - Patel, Hemangi (International Journal of Students’ Research in Technology & Management, 2015)
Toxic effluents containing synthetic dyes are discharged from various industries and they adversely affect water resources, soil fertility, aquatic organisms and ecosystem integrity. In this study, a novel bacterial consortium isolated from dye contaminated soil sample was shown to effectively decolorize Reactive Violet 5 and Golden Yellow HER within 22 hrs. under static condition at a maximum dye concentration of 400 mg/L and was named as B3RVY 3. Biochemical analysis and 16S rRNA sequencing was done for identification of the bacterial isolates responsible for degradation of the dyes. Dye decolorization was monitored using scanning Ultraviolet-Visible spectrophotometer which indicated that decolourization was due to the degradation of dyes into non-colored intermediates. The protein content estimation in raw dye and its degradation metabolites was performed and it was found that protein content increases with the increase in the concentration of the dye. Thus the stress is the main reason that shows the influence of protein content and responsible for degradation. Phytotoxicity study of both dyes on Vigna radiata and Triticum aestivum revealed the more toxic nature of raw dye and less toxic nature of its degradation metabolites. Microbial toxicity study on Escherichia coli and Staphylococcus aureus also showed the more toxic nature of raw dye and less toxic nature of its degradation metabolites.